2013
DOI: 10.1002/bdra.23124
|View full text |Cite
|
Sign up to set email alerts
|

Isolated atrioventricular canal defects: Birth outcomes and risk factors: A population‐based hungarian case–control study, 1980–1996

Abstract: Conduction disorders/cardiac dysrhythmias and chronic hypertension of mothers may have a role in the origin of AVCD, while high doses of folic acid in early pregnancy may reduce the risk of the development of AVCD. Birth Defects Research (Part A) 97:217-224, 2013. © 2013 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…All of the studies were published between 1989 and 2013. There were 14 case–control studies [28] [41] and 3 cohort studies [42] [44] . The main characteristics of the included studies are presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies were published between 1989 and 2013. There were 14 case–control studies [28] [41] and 3 cohort studies [42] [44] . The main characteristics of the included studies are presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the 3 cohort studies, cohort sizes varied from 22,365 [44] to 1,625,945 [43] , and the number of CHD cases ranged from 4,123 [44] to 12,101 [43] . In the 16 case–control studies, the number of cases varied from 81 [28] to 7,575 [32] , and the number of control subjects ranged from 302 [39] to 38,151 [41] . The highest parity number ranged from 2 [28] to more than 4 [39] .…”
Section: Resultsmentioning
confidence: 99%
“…The body of literature searched on the subject identified 26 studies which examined SES in relation to CHD development as listed in Table 1. The majority of the studies (18/26, 69%) examined individual maternal SES variables and the risk of CHD [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], whilst fewer (4/26, 15%) examined associations with SES at the area level or neighborhood level [38][39][40][41], and still others (4/26, 15%) examined the individual, family and neighborhood SES to weigh the relative contribution of each level of the SES variables in CHD development [42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…Education was the variable most commonly assessed in these studies and the findings were largely inconclusive with some reporting associations between maternal education and CHD [21,[26][27][28] and others finding no associations [25,29,30]. Low skilled occupations and low income similarly were associated with CHD in some studies [22,26,32,33,37] and not in others [20,23,24,30,31]. In the United States, Egbe et al reported interesting findings on the relationship between income and CHD, where they documented an increased incidence of mild CHD among Caucasian populations in the upper quartiles of SES [34][35][36] compared to non-Caucasian minority populations.…”
Section: Advances In Pediatric Researchmentioning
confidence: 94%
“…Thus, the objective of our project was to differentiate CHD entities and evaluate their possible risk factors 9 10. As the recently proposed CHD classifications are based on pathogenesis rather than anatomic location,11–13 we followed the CHD categorization in the Baltimore-Washington Infant Study 12.…”
Section: Introductionmentioning
confidence: 99%